SYSTEM AND METHOD FOR LOCATING AND DETERMINING SUBSTANCE USE - NIENHOUSE ROBERT FRANK (2018)
In devices that determine levels of substance use, a substance level in a test sample provided to the testing device by a test subject is determined. A sequence of images are captured to include a portion of the face of the test subject providing the test sample and a display of the testing device. A value indicative of the substance level detected within the test sample is determined. A validityindicator indicating validity of the value indicative of the substance level is determined. A current location is determined. The value indicative of the substance level, the validity indicator, and the current location are sent to a remote server. 在确定物质使用水平的装置中，确定测试对象提供到测试装置的测试样本中的物质水平。捕获包含提供所述测试样本的所述测试对象的面部的部分和所述测试装置的显示器的图像序列。确定指示在所述测试样本内检测到的所述物质水平的值。确定有效性指示符，其指示的是所述指示所述物质水平的值的有效性。确定当前方位。将所述指示所述物质水平的值、所述有效性指示符和所述当前方位发送到远程服务器。